Diversity of cave-dwelling pseudoscorpions from Guizhou in China, with the description of twenty-four new species of the genus Tyrannochthonius (Pseudoscorpiones, Chthoniidae) - Hou, Yanmeng; Feng, Zegang; Zhang, Feng (Zootaxa, 2023)
Twenty-four new Tyrannochthonius species from twenty-eight karst caves of Guizhou are described, including detailed diagnosis and illustrations: T. acutus sp. nov. from Gazuida Cave (Kaili City), T. altus sp. nov. from Shenren Cave (Hezhang County), T. arificus sp. nov. from Hei Cave (Anlong County), T. babaowanensis sp. nov. from Babaowan Cave (Yinjiang County), T. breviculus sp. nov. from Yanjia Cave (Libo County), T. brevispinus sp. nov. from Jingua Cave (Danzhai County), T. duo sp. nov. from Liangfeng Cave (Jiangkou County), T. gracilis sp. nov. from Xianren Cave (Hezhang County), T. hispidus sp. nov. from Qilin Cave (Jianhe County), T. infirmus sp. nov. from Liujiadadong Cave (Pu’an County), T. latus sp. nov. from Zimu Cave (Panzhou City), T. maculosus sp. nov. from Daxiao Cave (Xingren City), T. multicavus sp. nov. from Xiaohui Cave & Weier Cave (Pingtang County) and Da Cave & Qixia Cave (Luodian County), T. multidentatus sp. nov. from Guanyin Cave (Fenggang County) and Anjialin Cave (Sinan County), T. nanxingensis sp. nov. from Feng Cave (Panzhou City), T. oblongus sp. nov. from Houzi Cave (Huaxi District), T. parcidentatus sp. nov. from Daniu Cave (Dafang County), T. pictus sp. nov. from Gaoluo Cave and Cangjun Cave (Dushan County), T. pinguis sp. nov. from Zharou Cave (Ziyun County), T. planus sp. nov. from Yanggong Cave (Sandu County), T. qilinensis sp. nov. from Qilin Cave (Jianhe County), T. quattuor sp. nov. from Guanjiadadong Cave (Dafang County), T. umidus sp. nov. from Da Cave (Wudang District), and T. yanshanensis sp. nov. from Yanshan Cave (Wuchuan County). An identification key to all known Tyrannochthonius species from China is also provided.